Financial De-Dollarization : A Global Perspective and the Peruvian Experience - Catao, Luis (IMF Working Papers; Working Paper ;, 2016)
We re-appraise the cross-country evidence on the dollarization of financial systems in emerging market economies. Amidst striking heterogeneity of patterns across regions, we identify a broad global trend towards financial sector de-dollarization from the early 2000s to the eve of the global financial crisis of 2008-09. Since then, de-dollarization has broadly stalled or even reversed in many economies. Yet a few of them have continued to de-dollarize. This suggests that domestic factors are also important and interact with global factors. To gain insight into such an interaction, we examine the experience of Peru since the early 1990s and find that low global interest rates, low global risk-aversion, and high commodity prices have fostered de-dollarization. Domestic macro-prudential measures that raise the relative cost of domestic dollar loans and the introduction and adherence to inflation targeting have also been key.